Analysis of z-score nutritional indices and their association with stunting risk factors among toddlers aged 36–59 months - Hurun Ain; Faizul Hasan; Fitriana Kurniasari Solikhah (Pediomaternal Nursing Journal, 2026)
Introduction: Understanding the determinants of stunting is essential for setting priorities in developing evidence-based policies that improve child well-being and reduce its prevalence. Objective: This study aimed to analyze Z-score nutritional indices and their relationship with stunting risk factors among toddlers aged 36–59 months. Methods: This study employed a cross-sectional design. The study population consisted of 453 toddlers, from which a sample of 82 participants was determined using Yamane's formula. Samples were selected using a simple random sampling technique. The research was conducted in the catchment area of the Ardimulyo Community Health Center, Wonorejo Village, Singosari District, Malang Regency, Indonesia. Data were analyzed using the non-parametric Spearman's rank correlation test. Results: The findings revealed that most toddlers were not breastfed immediately after birth, the majority did not receive exclusive breastfeeding, and most mothers had only completed elementary education. A substantial proportion of toddlers had height-for-age Z-scores in the "short" category (≥ -3.0 to -2.0). Statistical analysis demonstrated that three factors were significantly associated with the Z-score index: (1) breastfeeding history, (2) sex, and (3) parental income. Conclusion: These findings indicate that, beyond birth weight and infectious diseases, other factors such as breastfeeding practices, gender, and socioeconomic conditions were significantly associated with stunting among toddlers. Further studies are recommended to explore additional contributing factors and to design targeted, context-specific interventions to prevent stunting in early childhood. Keywords: risk factors; stunting; toddlers; Z score index